Young Adult Pop Fiction: Empathy and the Twilight Series - Alicia Otano Unzue (European Journal of American Studies)
This analysis of the Twilight series focuses on the role of empathy as a communicative, cross-cultural tool by which the author transmits a message that features human commitment as the key to happiness. It also raises the issue of reader emotional neediness and authorial use of empathy in popular fiction to fuel consumption of the series in order to continue “feeling with” familiar and cherished characters. The readers that have made Stephenie Meyer’s Twilight series an international best-seller in the young adult/adolescent pop fiction market reflect the crucial role popular literature plays in their emotional experience. The message behind this pop fiction phenomenon is as ancient as its legendary vampire and shape-shifter characters yet its massive book sales warrant analysis of the author’s role in manipulating reader affect to successfully transmit her vision of attaining happiness. The study undertaken here on the role of empathy in the Twilight series attempts to contextualize this book phenomenon within the recent work of two specialists in the area of emotions in literature: Susanne Keen and Patrick Hogan and is also inspired by the underlying current of Martha Nussbaum’s work on the human ability to identify with others by means of empathy or compassion which is fomented through reading of fiction. Meyer has “tapped into the moment” in terms of what 21st century adolescents and young adults want to read about. By looking into the Twilight series and invoking features of its on-going plot and main characters it is possible to interpret how emotions are being used by the author to transmit a specific message on human commitment and how, ultimately, it is read and “felt” by the reader. In terms of emotions theory, my analysis works on the premise that pop fiction best-sellers cannot be ignored because they accurately reflect a vast area of human emotional life.